Taking up the quest for novel molecular solar thermal systems: Pros and cons of storing energy with cubane and cubadiene - Merino-Robledillo, Cecilia; Marazzi, Marco (Frontiers in Chemistry, 2023)
Molecular solar-thermal systems (MOSTs) are working their way as a possible technology to store solar light and release it when necessary. Such systems that could in principle constitute a solution to the energy storage problem characteristic of solar cells, are conceived, at a first instance, as simple molecular photoswitches. Nevertheless, the optimization of their different required properties is presently limiting their technological scale up. In the chemical perspective, we hence need to design novel MOSTs, based on unconventional photoswitches. Here, by applying multiconfigurational quantum chemistry methods, we unravel the potentialities of ad-hoc designed molecular photoswitches aimed to photoproduce cubane or cubadiene as high energy isomers that can be thermally (or eventually catalytically) reverted to the initial structure, releasing their stored energy. Especially, while cubane can be photoproduced via different paths depending on the reactant tricycle diene conformation, an undesired bicyclic by-product limits its application as MOST. An evolution of this starting design toward the formation cubadiene is therefore proposed, avoiding conformational equilibria and by-products, considerably red shifting the absorption to reach the visible portion of the solar spectrum, maintaining an estimated storage density expected to overcome the current MOST reference system (norbornadiene/quadricyclane), although consistently increasing the photoisomerization energy barrier.